Risk factors for tooth loss in adult Japanese dental patients: 8020 Promotion Foundation Study. Issue 2 (24th January 2019) - Saito, Mizuki; Shimazaki, Yoshihiro; Fukai, Kakuhiro; Furuta, Michiko; Aida, Jun; Ando, Yuichi; Miyazaki, Hideo; Kambara, Masaki
Abstract: Aim: The assessment of the risk of tooth loss in patients visiting a dental clinic is important for managing their oral health. In the present study, we examined the risk factors for tooth loss among dental patients. Methods: Data from the 8020 Promotion Foundation Study on the Health Promotion Effects of Dental Care were used in the present study. The study involved 2743 patients who visited a dental clinic in Japan and completed a questionnaire and oral health examination at baseline and at the 2‐year follow up. Tooth‐ and person‐level risk factors for tooth loss during 2 years were subjected to a multilevel multivariate logistic regression analysis. Results: In both the person‐ and tooth‐level analyses, age, smoking habit, reason for dental visit, economic status, number of remaining teeth, and periodontal status were significantly associated with tooth loss. In the tooth‐level analysis, tooth type, tooth status, and periodontal status were significantly related to tooth loss. Persons who visited a dental clinic for periodic maintenance had a significantly lower risk of tooth loss than those who visited only to receive dental treatment. Conclusions: Various tooth‐level factors and modifiable factors, such as smoking cessation and periodic maintenance, are important for the suppression of tooth loss in dental patients.